Endogenous fibrinolysis—Relevance to clinical thrombosis risk assessment. (16th December 2020) - Kanji, Rahim; Kubica, Jacek; Navarese, Eliano P.; Gorog, Diana A.
Abstract: The development of an obstructive luminal thrombus is pathological and considered a failure of endogenous fibrinolysis. The consequences may be fatal, or result in lasting downstream organ damage. Therefore, assessment of endogenous fibrinolytic status in an individual may identify those at risk of occlusive thrombus formation and provide prognostic information. Arterial thrombi are more platelet rich and more resistant to fibrinolysis than venous thrombi. Several recent studies using global tests of fibrinolysis in patients with acute coronary syndromes (ACS) have shown that despite dual antiplatelet therapy, patients with impaired fibrinolytic status have an increased risk of adverse cardiovascular events, compared with those with effective fibrinolytic function. Such data add significantly to the predictive value of established cardiovascular risk factors and conventional biomarkers. Most data reported have been obtained with the Global Thrombosis Test and the turbidimetric plasma clot lysis assay. A few small studies in patients with ischaemic stroke suggest a similar predictive role of fibrinolytic status assessment in these patients. Studies reporting an association between impaired fibrinolysis and future venous thrombotic events are limited, and in the form of case‐control studies. Viscoelastic assays may have a role in the prediction of venous thromboembolic risk. Assays of fibrinolytic function should be used to obtain a more accurate risk of future thrombotic events, particularly in the setting of ACS. The availability of point‐of‐care tests helps facilitate this and should encourage future studies to assess personalised antithrombotic treatment combinations to optimise fibrinolytic status and reduce thrombosis risk.